INTENSITAS SERANGAN DAN KOMUNITAS RAYAP TANAH DI KECAMATAN CIKAMPEK - Ginuk Sumami; Agus Ismanto (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The study was carried out at Cikampek on three different soil types namely Red Latosol, Redish Brown Latosol and Lateritie Association; Complex of Yellowish Red Podzolic, Yellow Podzolic and Regosol; Complex of Grumusol, Regosol and Mediteran.Odontotermes grandiceps Holmgren, Microtermes insperatus Kemner and Macrotermes gilvus (Hagen) seems to be common species in the above locations. The highest density was found on Complex of Yellowish Red Podzolic, Yellow Podzolic and Regosol (123 termites per test block), while the lowest one was found on Complex of Grumusol, Regosol and Mediteran (14 termites per test block). Termite attack intensity during the first, second, third and fourth period of observation in the three soil types were different.